2021
DOI: 10.1109/access.2021.3072481
|View full text |Cite
|
Sign up to set email alerts
|

Beamforming and Reflection Coefficient Control for Multiantenna Backscatter Communication With Nonorthogonal Multiple Access

Abstract: For ultralow-power Internet of Things, we consider a monostatic multiantenna backscatter communication network (MBCN) supporting massive devices through nonorthogonal multiple access (NOMA) over space division multiple access (SDMA). For the network, we optimize the transmit beamforming (BF) for signal excitation of a reader, reflection coefficients of devices for backscattering and energy harvesting, and receive BF for information decoding at the reader toward the maximum fairness in data collection. We first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Driven by the potential and popularity of the integration of the PD-NOMA scheme and monostatic BackCom, several studies have recently addressed the design and performance evaluation for static NOMA-aided monostatic BackCom systems [22], [23], [24], [25], [26]. Particularly, Jing et al provided the design guideline for the monostatic Back-Com systems using a hybrid time-division multiple-access (TDMA)/PD-NOMA scheme, where the reflection coefficients for the multiplexed BNs from different NOMA groups are set to different values to utilize the PD-NOMA [22].…”
Section: ) Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Driven by the potential and popularity of the integration of the PD-NOMA scheme and monostatic BackCom, several studies have recently addressed the design and performance evaluation for static NOMA-aided monostatic BackCom systems [22], [23], [24], [25], [26]. Particularly, Jing et al provided the design guideline for the monostatic Back-Com systems using a hybrid time-division multiple-access (TDMA)/PD-NOMA scheme, where the reflection coefficients for the multiplexed BNs from different NOMA groups are set to different values to utilize the PD-NOMA [22].…”
Section: ) Related Workmentioning
confidence: 99%
“…In [23], the authors introduced a mechanism to reduce the collisions in NOMA-aided BackCom systems, where a power level threshold for BNs was considered in the backscattering phase. The authors in [24] addressed the performance of NOMA-aided monostatic multiantenna BackCom systems, in which a space division multiple access (SDMA) scheme was employed. In [25], the authors presented a transmitted power-driven channel access scheme, which controls the number of BNs contending the channel by tuning the transmitted power of the illuminator incrementally.…”
Section: ) Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [11], Elsayed et al derived exact and asymptotic closed-form OP solution for symbiotic-radio users, who wish to receive signals from both primary and secondary transmitters, when the system operates in Nakagami-m fading medium. In [13], Sacarelo et al provided a guidance framework on jointly optimizing the transmit beamforming weights and backscattering coefficients to achieve the maximum rate fairness in a monostatic multi-antenna AmBC-enabled NOMA systems. In [14], Le et al showed the advantages of AmBC-enabled NOMA in conjunction with cognitive radio (CR) networks to achieve high spectrum utilization, where a base station cognitively communicates with two secondary users via a relay node capable of collect/decode and backscatter its received signal simultaneously.…”
Section: Introductionmentioning
confidence: 99%